Quality Culture the Key to Quality Improvement - Jan Stefanik (Communications - Scientific letters of the University of Zilina, 1999)
Quality culture is the total of the collective or shared learning of quality-related values as the organization develops its capacity to survive in its external environment and to manage its own internal affairs.